2001
DOI: 10.1515/znc-2001-11-1203
|View full text |Cite
|
Sign up to set email alerts
|

A New Pyoverdin from Pseudomonas aeruginosa R'

Abstract: From a Pseudom onas aeruginosa hospital isolate a new pyoverdin was isolated. It is iden­tical with that of Pseudomonas aeruginosa strain R except that in the peptide chain L-Gln is missing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Previous work showed that RЈ synthesizes a rare fourth type of pyoverdine, a type III pyoverdine with a missing glutamine residue (61). Consistent with these findings, RЈ has a type III sequence type with a deletion of one nonribosomal peptide synthetase cassette, whose predicted specificity is glutamine.…”
supporting
confidence: 75%
“…Previous work showed that RЈ synthesizes a rare fourth type of pyoverdine, a type III pyoverdine with a missing glutamine residue (61). Consistent with these findings, RЈ has a type III sequence type with a deletion of one nonribosomal peptide synthetase cassette, whose predicted specificity is glutamine.…”
supporting
confidence: 75%
“…Indeed, given the specificity for a membrane receptor that always has to recognize its pyoverdin, it seems probable that the pyoverdins evolve predominantly by replacement, loss, or acquisition of one amino acid. As shown with structurally related typical pyoverdins (2,31,33,39), the membrane receptor could probably still incorporate a slightly modified pyoverdin.…”
Section: Discussionmentioning
confidence: 88%
“…The results of the amino acid and MS analyses strongly suggest that such a modification probably occurred in the pyoverdins of P. syringae and P. cichorii, with replacement of a serine by a glycine or vice versa. Differences of one amino acid between typical pyoverdins were observed in P. aeruginosa and in P. fluorescens (31,39). In both cases, the pyoverdins differed essentially in terms of the presence of one additional amino acid in one of the molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations